Development and Evaluation of Passive Balancing System Model for Lithium-Ion Battery Pack in Electric Vehicles Using Numerical Simulation - Vu Háº£i Quan; Karpukhin Kirill Evgenievich; Nguyen Trong Duc; Karpukhin Filipp Kirillovich (Automotive Experiences, 2025)
Electric vehicles (EVs) are increasingly becoming a crucial solution to mitigate environmental pollution and ensure energy security. Batteries, particularly Lithium-ion batteries, are the core component that determines the performance, range, and durability of EVs. However, managing and balancing the state of charge (SOC) among hundreds of cells in a battery pack is a significant challenge due to its complexity and high accuracy requirements. This study addresses these gaps by developing an integrated electro-thermal passive balancing model that combines Thevenin equivalent circuit modeling with dynamic thermal analysis and Stateflow-based MOSFET control logic, specifically designed for EV battery pack applications under realistic urban driving cycles. The passive voltage balancing process is designed to maintain voltage homogeneity among cells, thereby enhancing the pack's efficiency and lifespan. Initial assumptions are made to reduce model complexity (3 Lithium-ion cells), although this may lead to some discrepancies with real-world scenarios. Simulation results show that charging and discharging processes are efficiently managed, with SOC balancing among cells being maintained nearly perfectly after several cycles. Voltage, current, and temperature plots demonstrate stability and uniformity in cell operation thanks to the passive balancing mechanism. However, the current model is limited in reflecting real-world conditions, such as continuous changes in speed and load when the vehicle is in motion. This study provides insights into the operation of EV battery packs through electro-thermal modeling, while suggesting future directions to improve the model's realism and applicability in diverse operating scenarios. The results emphasize the importance of cell balancing in optimizing performance and prolonging the lifespan of EV battery systems.